The Role of Religious Moderation in Improving the Morale of the Millennial Generation: A Study of Hijra Youth in Semarang - Multazam, Multazam; Mubarok, Zaim El; Qutni, Darul; Shofwan, Imam (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2024)
This article aims to examine the role of religious moderation to improving the morale of the millennial generation and helping them become better people. This study used a descriptive-qualitative research methodology. Research data were collected through interviews with questionnaires, non-participant observations, and documentation. The study informants numbered 10 participants (7 men and 3 women) aged 24 to 30 years. Research findings show that diversity can lead to various conflicts if society cannot find a middle ground for everything. These problems can be solved with religious tolerance and moderation to create peace and harmony in society. People who do not have knowledge of religious moderation and good religious foundations will have morals that are not in accordance with religious values, for example, drug addiction and bullying. Both actions are basically driven by environmental factors. In Islam, drugs and bullying are things that have a lot of mudharat, so it is forbidden to do so. However, those who are willing to leave both should not be excluded so that they feel that their change has the support of their surroundings. A society that has a strong knowledge base of religious moderation and faith will always embrace it so that a life of peace, tolerance, and mutual respect can be created.